A simple and effective isocratic HPLC method for fast identification and quantification of surfactin - Muhammad Qadri Effendy Mubarak,; Abdul Rahman Hassan,; Aidil Abdul Hamid,; Sahaid Khalil,; Mohd Hafez Mohd Isa, (Universiti Kebangsaan Malaysia, 2015)
The aim of this study was to establish a simple, accurate and reproducible method for the identification and quantification of surfactin using high-performance liquid chromatography (HPLC). Previously reported method of identification and quantification of surfactin were time consuming and requires a large quantity of mobile phase. The new method was achieved by application of Chromolith® high performance RP-18 (100 × 4.6 mm, 5 μm) as the stationary phase and optimization of mobile phase ratio and flow rate. Mobile phase consisted of acetonitrile (ACN) and 3.8 mM trifluroacetic acid (TFA) solution of 80:20 ratio at flow rate of 2.2 mL/min was obtained as the optimal conditions. Total elution time of the obtained surfactin peaks was four times quicker than various methods previously reported in the literature. The method described here allowed for fine separation of surfactin in standard sample (98% purity) and surfactin in fermentation broth.